Influence of drought hardening on the resistance physiology of potato seedlings under drought stress - Shu-han ZHANG; Xue-feng XU; Ye-min SUN; Jun-lian ZHANG; Chao-zhou LI (Journal of Integrative Agriculture, 2018)
In this paper, the influence of drought hardening on the growth, development, resistance physiology, leaf microstructure and stomatal behavior of potato seedlings under drought stress was studied, and the mechanism of drought hardening improvement of potato seedling drought resistance was elucidated. We found that drought stress had several adverse effects on potato seedlings, yet drought hardening alleviated the decrease in relative water content (RWC), net photosynthetic rate (Pn) and chlorophyll content and inhibited the increase in relative electric conductivity and malondialdehyde (MDA) content. Compared with contrast seedlings, drought-hardened seedlings also had enhanced root vigor, increased antioxidant enzyme activity and higher levels of abscisic acid (ABA), proline (Pro), soluble sugars and polyamines (PAs) under drought stress. In addition, the stomatal density of potato seedling leaves increased significantly, while the leaf area, stomatal size and stomatal aperture decreased with drought hardening treatment. These changes led to reduced leaf transpiration rate (Tr) and improved water utilization efficiency (WUE). The changes in leaf microstructure also had a positive effect on the drought resistance of the drought-hardened potato seedlings. So it can be concluded that through increasing the content of some endogenous hormones, osmotic regulatory substances and the activities of antioxidant enzymes, the resistance physiology of drought-hardened potato seedlings was enhanced.